Circadian Phase Advances in Response to Weekend Morning Light in Adolescents With Short Sleep and Late Bedtimes on School Nights - Misiunaite, Ieva; Eastman, Charmane I.; Crowley, Stephanie J. (Frontiers in Neuroscience, 2020)
Many adolescents fall asleep too late to get enough sleep (8–10 h) on school nights. Morning bright light advances circadian rhythms and could help adolescents fall asleep earlier. Morning bright light treatment before school, however, is difficult to fit into their morning schedule; weekends are more feasible. We examined phase advances in response to morning light treatment delivered over one weekend. Thirty-seven adolescents (16 males; 14.7–18.0 years) who reported short school-night sleep (≤7 h) and late bedtimes (school-nights ≥23:00; weekend/non-school nights ≥24:00) slept as usual at home for ∼2 weeks (“baseline”) and then kept a fixed sleep schedule (baseline school-night bed and wake-up times ±30 min) for ∼1 week before living in the lab for one weekend. Sleep behavior was measured with wrist actigraphy and sleep diary. On Saturday morning, we woke each participant 1 h after his/her midpoint of baseline weekend/non-school night sleep and 1 h earlier on Sunday. They remained in dim room light (∼20 lux) or received 1.5 or 2.5 h of intermittent morning bright light (∼6000 lux) on both mornings. The dim light melatonin onset (DLMO), a phase marker of the circadian timing system, was measured on Friday and Sunday evenings to compute the weekend circadian phase shift. The dim room light and 1.5-h bright light groups advanced the same amount (0.6 ± 0.4 and 0.6 ± 0.5 h). The 2.5-h bright light group advanced 1.0 ± 0.4 h, which was significantly more than the other groups. These data suggest that it is possible to phase advance the circadian clock of adolescents who have late bedtimes and short school-night sleep in one weekend using light that begins shortly after their sleep midpoint.